Evaluating the genetic consequences of population subdivision as it unfolds and how to best mitigate them: A rare story about koalas. Issue 9 (13th March 2023) - Frère, C. H.; O'Reilly, G. D.; Strickland, K.; Schultz, A.; Hohwieler, K.; Hanger, J.; de Villiers, D.; Cristescu, R.; Powell, D.; Sherwin, W.
Abstract: The genetic consequences of the subdivision of populations are regarded as significant to long‐term evolution, and research has shown that the scale and speed at which this is now occurring is critically reducing the adaptive potential of most species which inhabit human‐impacted landscapes. Here, we provide a rare and, to our knowledge, the first analysis of this process while it is happening and demonstrate a method of evaluating the effect of mitigation measures such as fauna crossings. We did this by using an extensive genetic data set collected from a koala population which was intensely monitored during the construction of linear transport infrastructure which resulted in the subdivision of their population. First, we found that both allelic richness and effective population size decreased through the process of population subdivision. Second, we predicted the extent to which genetic drift could impact genetic diversity over time and showed that after only 10 generations the resulting two subdivided populations could experience between 12% and 69% loss in genetic diversity. Lastly, using forward simulations we estimated that a minimum of eight koalas would need to disperse from each side of the subdivision per generation to maintain genetic connectivity close to zero but that 16 koalas would ensure that both genetic connectivity and diversity remained unchanged. These results have important consequences for the genetic management of species in human‐impacted landscapes by showing which genetic metrics are best to identify immediate loss in genetic diversity and how to evaluate the effectiveness of any mitigation measures.